EVERYBODY COUNTS: THE RIGHT TO VOTE OF PERSONS WITH PSYCHOSOCIAL DISABILITIES IN SOUTH AFRICA (African Disability Rights Yearbook, 2021)
Persons with psychosocial disabilities were historically denied the right to vote due to the long-held perception that they do not have the required decision-making capabilities required for voting. The adoption of the UN Convention on the Rights of Persons with Disabilities (CRPD) in 2006 has necessitated a re-examination of this perception, leading to the growing recognition internationally that a universal limitation on the right to vote of persons with psychosocial disabilities can no longer be justified. This article accordingly examines the right to vote of persons with psychosocial disabilities in South Africa, which is generally regarded as an exemplary electoral model in the African region. The South African Constitution guarantees universal suffrage; at the same time, persons who are regarding as being ‘of unsound mind’ are excluded from voting. The article considers this ‘systemic electoral inconsistency’ against the paradigm shift mandated by the CRPD (and to some extent presaged by earlier international instruments). The traditional justifications for excluding persons with psychosocial disabilities from voting are weighed against the contemporary notions of legal capacity and decision-making, again with reference to the CRPD and recent interpretations by the Committee on the Rights of Persons with Disabilities.